Transactional distance in a flexible learning environment: Scale development and validation in the Philippine context - Jose Z. Tria (Knowledge Management & E-Learning: An International Journal, 2024)
The aim of this paper is to develop a reliable and valid transactional distance scale in a flexible learning environment from the perspectives of students of a higher education institution in the Philippines. To achieve this goal, the researcher assessed the construct validity and reliability of the scale by using the exploratory factor analysis (EFA) and confirmatory factor analysis (CFA). Additionally, Cronbach alpha was used to test the internal consistency of the items. The model revealed three-factor structure anchored on Moore’s Transactional Distance theory namely structure, learner autonomy and dialogue. The model validates the previously extracted factors along with the items. The findings of this study revealed that the implementation of flexible learning in the Philippine context is a multidimensional construct and serves as a critical success factors. The proposed transactional distance scale in a flexible learning environment may serve to facilitate the implementation of flexible learning in higher education institutions thereby implementing flexible learning effectively and efficiently. Little literature and studies exist on the implementation of flexible learning anchored on transactional distance theory. Thus, this attempts to bridge this gap in the existing literature and studies. This three-factor model of flexible learning in a higher education institution anchored on Transactional Distance Theory would be a useful tool to assess the perception of students towards the implementation of flexible learning in a new normal environment.